Implementasi Supervisi Akademik untuk Meningkatan Kompetensi Sumber Daya Manusia (Guru) dalam Kegiatan Belajar Mengajar - Suharto Suharto (Publikasi Indonesia, 2023)
This study aims to explore the importance of teaching and learning activities in the educational process in schools and how teachers can improve student achievement through the application of appropriate teaching and learning strategies. The text discusses that the success of educational attainment depends largely on the quality of the learning process involving intellectual, emotional and behavioral aspects of students. Education is a conscious and planned effort to develop students' potential in various aspects of life. To improve learning achievement, teachers need to master the class during the learning process by choosing strategies, models, and learning media that suit students' interests and abilities. Teachers are also the main human resources in improving the quality of education in schools and need to be managed properly through managerial and operational functions in human resource management (HRM). Work as a teacher is a professional job, so a professional teacher must have four competencies, namely pedagogic, personality, social, and professional competencies. This research can contribute to improving the quality of the learning process and student achievement in schools.